FASE-1: IMPLEMENTASI STANDAR ATURAN PEMODELAN UML SEBAGAI DASAR SPESIFIKASI KEBUTUHAN DI EFARMING CORPORA BANDUNG - Gede Agung Ary Wisudiawan; Mahendra Dwifebri Purbolaksono; Pramoedya Syachrizalhaq Lyanda; Yudi Priyadi (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
In Phase 1 of this Abdimas, activities focused on the general analysis presented through system modeling rules and data modeling. This activity will have an impact on the next Abdimas phases. There is a problem focus on how to describe the system and the process of sending data. There was a problem in analyzing the requirements specifications in the process of sending agricultural activist data to its members. In general, the objectives regarding the potential/opportunities for empowerment of farmer members in the EFarming Corpora community can be increased by identifying requirements specifications, which will be defined through the creation of system modeling and data modeling. There is an adoption of the method through modification is carried out for Phase 1 of the Regular Scheme of community service activities, which will provide understanding to farmer activists in the Bandung Corpora Efarming Environment regarding information technology to support Farmer Community activities. The discussion of material implemented in this community service partner includes several supporting results in the next phase. This discussion is the basis for development that can be explored in the System Development Life Cycle stage, through the support of the Software Requirement Specification, Elicitation, Requirement Statement, Software Modeling, and Software Prototype. In its implementation, for Phase 1, Abdimas has a form of activity resulting from several activities: scientific training, a compilation of required information systems, and surveys and analysis of industrial needs.